An Examination Of Executive Directors' Remuneration Of Public Listed Companies In Malaysia - Ooi, Chye Khoon (2008)
The issue of executive director's remuneration has been the subject of debate in recent years. This study investigates the determinants of executive director's remuneration using all the public companies listed on the main board of Bursa Malaysia from 2004 to 2006.